Pengaruh Brand Image dan Kualitas Produk terhadap Keputusan Pembelian Produk Motor Matic Honda - Muhammad Faturrahman Rifai Rahmat; Moh. Mukhsin (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
This study aims to identify the impact of brand image and product quality on Honda's matic motorcycle purchase decisions, viewed from an Islamic perspective. This study was conducted at Sultan Ageng Tirtayasa University with a population consisting of students majoring in Sharia Economics. The type of research conducted is quantitative descriptive, with sampling using probability sampling techniques. The study findings indicated that the decision-making process is influenced by both the brand image and the quality of the product in tandem to purchase Honda matic motors in Sharia Economics students at Sultan Ageng Tirtayasa University from an Islamic perspective. This finding is supported by the compute's F value of 11,520, which is much larger than the table's F value of 3.15. This indicates The combined impact of brand image and product quality significantly influences the purchasing decision of Honda's automatic motorcycles, especially When viewed from the perspective of Islamic principles within the scope of Sharia Economics.